2008
DOI: 10.1007/s00253-008-1492-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a stress-inducible Dunaliella salina Lcy-β gene encoding a functional lycopene β-cyclase

Abstract: The halotolerant green alga Dunaliella salina accumulates large amounts of beta-carotene when exposed to various stress conditions. Although several studies concerning accumulation and biotechnological production of beta-carotene have been published, the molecular basis and regulation of the genes involved in carotenoid biosynthesis in D. salina are still poorly known. In this paper, we report the isolation and regulation of the lycopene beta-cyclase (Lcy-beta) gene by abiotic stress. The function of this gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 44 publications
8
43
1
1
Order By: Relevance
“…-carotene content mainly followed the same tendency [COESEL et al, 2008]. Our data on -carotene accumulation in the free of nutrients culture media confirmed that pattern.This molecular data brought the authors to the conclusion that nutrient depletion is necessary and sufficient for induction of -carotene accumulation in D. salina cells at transcriptional level [COESEL et al, 2008]. Our data add to this finding that nutrient…”
supporting
confidence: 86%
See 3 more Smart Citations
“…-carotene content mainly followed the same tendency [COESEL et al, 2008]. Our data on -carotene accumulation in the free of nutrients culture media confirmed that pattern.This molecular data brought the authors to the conclusion that nutrient depletion is necessary and sufficient for induction of -carotene accumulation in D. salina cells at transcriptional level [COESEL et al, 2008]. Our data add to this finding that nutrient…”
supporting
confidence: 86%
“…This molecular data brought the authors to the conclusion that nutrient depletion is necessary and sufficient for induction of -carotene accumulation in D. salina cells at transcriptional level [COESEL et al, 2008]. Our data add to this finding that nutrient…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…NRC-1 (19), Haloarcula marismortui (18), Halobacterium salinarum (22), uncultured marine bacterium 66A03 (16), and uncultured marine bacterium HF10 49E08 (21). ␤-Carotene biosynthetic genes crtE, crtB, crtI, crtY, ispA, and idi encode the enzymes necessary for the synthesis of ␤-carotene from isopentenyl diphosphate, and the Idi, IspA, CrtE, CrtB, CrtI, and CrtY proteins have been characterized in vitro (23)(24)(25)(26)(27)(28). Blh protein has been proposed to catalyze or regulate the conversion of ␤-carotene to retinal (29, 30), but there is no direct proof of the enzymatic activity.…”
mentioning
confidence: 99%